Is the expulsion of women as foreigners in Ezra 9-10 justifiably convenantal? - Emmanuel Usue (Acta Theologica)
A surface reading of Ezra 9-10 gives the impression that the Abrahamic and Mosaic covenants’ codes concerning foreigners justify the expulsion of the so-called foreign women by Ezra and his associates. Consequently, the story has generated various viewpoints among Old Testament scholars. However, in this article, the author has attempted to show that Ezra and his associates did not provide convincing reasons for these massive expulsions. Rather, it appears, the expulsion was based upon a partial or narrower view and interpretation of the Abrahamic and Mosaic covenants’ codes concerning foreigners. A close reading of the story and the purported covenants’ codes concerning foreigners reveals that first, these women were not foreigners as presupposed by Ezra and his associates; second, had the reformers adopted a more holistic or broader perspective and interpretation of the Abrahamic and Mosaic covenants’ codes about foreigners, it would have yielded a more positive, accommodating and inclusive disposition towards the so-called foreign women.